A sporadic sodium layer event detected with five‐directional lidar and simultaneous wind, electron density, and electric field observation at Tromsø, Norway. Issue 21 (11th November 2015) - Tsuda, T. T.; Nozawa, S.; Kawahara, T. D.; Kawabata, T.; Saito, N.; Wada, S.; Hall, C. M.; Tsutsumi, M.; Ogawa, Y.; Oyama, S.; Takahashi, T.; Ejiri, M. K.; et al.
Abstract: A sporadic sodium layer (SSL) was detected with five‐directional lidar observation on 15 December 2012 at Tromsø, Norway. We have derived the horizontal velocity of the SSL front from the SSL onset times at the five positions and compared it with the background wind velocity from the collocated meteor radar and European Incoherent Scatter (EISCAT) radar. As a result, both velocities were fairly consistent. The increase rate in the height‐integrated sodium density around the SSL onset was 3–6 ×10 10  m −2  s −1, which was comparable to relatively large cases in the previous studies. However, the EISCAT‐observed electric field was too small to induce such a rapid sodium atom production. In addition, the amounts of the sodium atom increases at the five positions were mostly same. Thus, there were no clear signatures for the sodium atom production. These results strongly indicate that the observed SSL was just advected by the background wind. Key Points: First observational evidence for horizontal advection of the sporadic Na layer in polar region Separation of temporal/spatial variations in the sporadic Na layer by multidirectional lidar system Background conditions in neutral wind and electric field around the onset of the sporadic Na layer